Deposit Formation in Georgia - Tchaidze, Robert; Tvalodze, Salome (Washington, D.C. : International Monetary Fund, 2011)
This paper analyzes behavior of the real deposits in Georgia in1996-2009 by modeling demand for the real broad money balances and the cash-deposit ratio. The results suggest that the main factors that affected deposits over those years were income, development of the financial sector, and changes in the tax burden, while changes in the interest rate and inflation played only a minor role. The results also demonstrate importance of the geopolitical events as they affect confidence in the banking sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet